Traffic Bottlenecks: Predicting Atmospheric Blocking With a Diminishing Flow Capacity - Xingjian Yan; Lei Wang; Edwin P. Gerber; Valentina Castañeda; Ka Ying Ho (Geophysical Research Letters)
Abstract Atmospheric blocking is characterized by persistent anticyclones that “block” the midlatitude jet stream, causing temperature and precipitation extremes. The traffic jam theory posits that blocking events occur when the Local Wave Activity flux, a measure of storm activity, exceeds the carrying capacity of the jet stream, leading to a pile up. The theory's efficacy for prediction is tested with atmospheric reanalysis by defining “exceedance events”, the time and location where wave activity first exceeds flow capacity. The theory captures the Northern Hemisphere winter blocking climatology, with strong spatial correlation between exceedance and blocking events. Both events are favored not only by low carrying capacity (narrow roads), but also a downstream reduction in capacity (lane closures causing a bottleneck). The theory fails, however, to accurately predict blocking events in time. Exceedance events are not a useful predictor of an imminent block, suggesting that confounding factors explain their shared climatological structure.